A new bathyal Fusinus (Mollusca: Gastropoda: Fasciolariidae) from New Caledonia - Snyder, Martin A.; Hadorn, Roland (Zootaxa, 2006)
A new bathyal species of Fusinus is described from New Caledonia. Fusinus laviniae new species is distinguished from other New Caledonia Fusinus by its long siphonal canal and angular sculpture. This new species is compared to F. colus (Linnaeus, 1758), F. nicobaricus (Röding, 1798), F. nobilis (Reeve, 1847), F. salisburyi Fulton, 1930, F. similis (Baird, 1873), and F. undatus, (Gmelin, 1791). A range extension for F. nobilis to New Caledonia is noted.